Effectiveness of Bilingual Practices in English Language Classroom: Perception of the Teachers and the Students - Niaz, Fazeelat; Fatima, Syeda Maryam; Farooq, Muhammad (Annals of Human and Social Sciences, 2023)
This research studied the perception of Pakistani English language (EL) students and teachers regarding the effectiveness of bilingual practices in the EL tutorial room. The data collection tools were questionnaires and interviews. The participants were 120 students and ten teachers at WUAJK, Pakistan. Analysis of data revealed that there were resemblances in the perceptions of the teachers and the students about the effectiveness of bilingual practices. The study showed that Pakistani EL students and teachers were willing to use L1 practice in the English language tutorial room. Teachers and students believed that the medium of instruction must be English. They should keep the limited use of L1 practice in EL classrooms whenever it is beneficial to relieve anxiety and create a comfortable environment for the participation of reluctant students and students with low confidence. So, using bilingual practices is effective in English language learning. The limited use of L1 assists in learning of English language and does not reduce the English language learning process.